Influence of kinematic parameters on result efficiency in javelin throw - Saratlija, P.; Zagorac, N.; Babic, V. (Collegium Antropologicum, 2013)
The aim of the research was to define the influence of the kinematic parameters in the javelin throw success in the top junior athletes at the European Junior Athletics Championships in Novi Sad. A set, consisting of 17 kinematic variables, was applied on a sample of 16 athletes, and the same variables were registered at the 2009 Novi Sad European Junior Championships. The criteria variable was the achieved throw length (javelin throw). The subjects were represented by 113 successful javelin throws. The results of the chosen kinematic variables correlation analysis showed the existence of multiple significant relations between the observed variables. Based on the observed kinematic variables correlation analysis, the next conclusion can be made: the javelin release speed has the most important role, followed by the fast front support leg placing. The results are expected and logical, and can be used in kinesiology practice, especially in the process of young throwers' technique learning and in development of motor abilities relevant for this athletic discipline.